Deficiencies in Nutritional Intake in Patients with Diabetic Foot Ulcers - Maier, Haiyan M.; Ernst, Jasminka Ilich; Arjmandi, Bahram; Kim, Jeong Su; Spicer, Maria T. (Journal of Nutritional Therapeutics, 2017)
Aims: This study examined the dietary and anthropometric components of diabetic patients with or without diabetic foot ulcers (DFU). Methods: Eighty-two adult subjects were recruited in Tallahassee, FL (USA) and categorized into one of three groups: subjects without diabetes, patients with Diabetes Mellitus (DM) but not foot ulcers, and patients with DFU. Twenty-four hour food recalls, foot ulcer history and blood samples were collected from each subject. Dietary intake was evaluated with Food Processor. Biomarkers of inflammation and oxidative stress were measured with ELISA kits. Results: DFU subjects in this study were mostly overweight or obese. DFU had inadequate intakes in protein, fiber, vitamin B1, B2, B3, B6, C, D, and E; calcium, magnesium, phosphorus, potassium, selenium, and zinc. They had excessive intakes in saturated fat, trans fat, and sodium. Conclusions: Malnutrition is very common in the DM and DFU subjects. Protein and vitamin supplementation may be beneficial in prevention and management of DM as well as DFU.